TECHNIQUES OF SOLVING RATIONAL INEQUALITIES - Al Jupri (ALGORITMA: Journal of Mathematics Education, 2021)
The topic of rational inequalities is taught at high school and university mathematics. Both high school students and college students still have difficulty solving rational inequalities. This study aims to describe techniques for solving rational inequalities. To reach this aim, a qualitative study using the document analysis method was carried out. Analyzed documents in this study include secondary school mathematics textbooks, test preparation textbooks for university entrance, Calculus and Basic Mathematics for university students’ textbooks, and relevant articles on rational inequalities. The results of this study included descriptions of techniques for solving rational inequalities,  including the techniques of number line, of analysis, and of graph aided with the GeoGebra software. It can be concluded that the three techniques of solving rational inequalities complement each other for understanding the meaning and the process of solving rational inequalities.